An in-depth look into today drugs - Mohammad, Norsarwany (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2012)
The absence of significant different in the rate and extent to which the active ingredient in pharmaceutical equivalent or pharmacologic alternatives become available at the site of drug action. To be BE, 90% confident interval with AUC and Cmax of the test drug must fall within 80% to 125% of the reference standard (innovator). Bioequivalent should be done for generic drugs.